2022
DOI: 10.1177/10225536221078622
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration pneumonia and anesthesia techniques in hip fracture surgery in elderly patients: A retrospective cohort study using administrative data

Abstract: Purpose: Aspiration pneumonia is a critical issue. General anesthesia may suppress the airway’s protective reflex. However, aspiration pneumonia is also observed in patients who undergo hip fracture surgery under spinal anesthesia. The aim of this study was to investigate the relationship between anesthesia methods and aspiration pneumonia as well as the predictive factors of aspiration pneumonia in elderly patients undergoing hip fracture surgery. Methods: The medical records of 19,809 patients aged ≥60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…And reducing postoperative complications and hospitalization time are important indicators for accelerating postoperative rehabilitation. There are studies have reported that SA may be associated with a reduced incidence of postoperative complications, including death, deep vein thrombosis, pulmonary complications, and myocardial infarction (2,3,12,15,18), which aligns with our results. Selection bias is an obvious limitation of observational studies, resulting in unreliable results if improperly addressed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…And reducing postoperative complications and hospitalization time are important indicators for accelerating postoperative rehabilitation. There are studies have reported that SA may be associated with a reduced incidence of postoperative complications, including death, deep vein thrombosis, pulmonary complications, and myocardial infarction (2,3,12,15,18), which aligns with our results. Selection bias is an obvious limitation of observational studies, resulting in unreliable results if improperly addressed.…”
Section: Discussionsupporting
confidence: 92%
“…The main outcome of this study was the incidence of postoperative self-care. According to the results of previous literature ( 12 ), GA (48%) and SA (31%), a minimum of 258 evaluable patients (129 per arm) would be required to detect a difference between the two groups at p = 0.05 (2-tailed), with a power of 90%. Thus, the sample size is enough for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…[35] However, several studies have found no relationship between different anesthetic techniques and POP in elderly patients undergoing hip fracture surgery. [36,37] This study also did not find any effect of anesthesia on POP. Therefore, future large prospective studies Our study indicates that elderly hip fracture patients with preoperative Hb levels < 83.5 g/L should be considered for blood transfusions to reduce the occurrence of POP.…”
Section: Discussionmentioning
confidence: 49%
“…[35] However, several studies have found no relationship between different anesthetic techniques and POP in elderly patients undergoing hip fracture surgery. [36,37] This study also did not find any effect of anesthesia on POP. Therefore, future large prospective studies are necessary to explore the effect of the anesthesia modality on POP in elderly patients with hip fractures.…”
Section: Discussionmentioning
confidence: 52%
“…Studies in the last five years have suggested that the incidence of pneumonia in patients who undergo GA for hip fracture surgery is similar to that in patients who undergo neuraxial anesthesia for this procedure [ 5 , 8 , 11 ]. Acute upper and lower respiratory infection may significantly reduce postoperative quality of life and impair the recovery of geriatric patients with lower-limb fractures [ 12 ]; however, the literature has mostly focused on the pulmonary complications after fracture surgery and few have mentioned the incidence of ARI during a short postoperative period, which may be related to the late respiratory complications and may need to be carefully prevented during the COVID-19 pandemic. This study aims to clarify how different anesthesia methods influence the incidence of ARI during the one-month postoperative period and to identify the related risk factors.…”
Section: Introductionmentioning
confidence: 99%